ULAMA DALAM PERSPEKTIF AL-QUR’AN - Ahmad Deski (Institut Darul Quran Payakumbuh, 2017)
The purpose of the research is to discuss ulama in Islamic society. Ulama in Islam has an important position and role in spreading out and teaching Islam in the middle of society. In the case, the prophet Muhammad states in his hadiths that ulama is the heritage of the prophet. As the heritage of prophet, ulama has a very heavy duty and responsibility, not all human beings can be ulama. In this article, the writer discusses what is an ulama from the perspective of al-Quran. The word ulama is a plural noun of the singular one, `âlim. The word `âlim is ism fâ`il of the word `ilm/`alima means understanding clearly and surely. In al-Quran, the word `ilm/`alima in various derivations is repeated 854 times. Meanwhile, the word al-`ulamâ’ is the plural form of al-`âlim, in al-Quran is repeated twice: Quran, al-Syu’ara’ (26):197 and Quran, Fathir (35): 28. The meaning of ulama in this verse is someone who masters a study of Allah and syariah (Qur’aniyah verse), knowledge of natural and social phenomenon (kauniyah verse), and has sense of khasyyah.